2012
DOI: 10.2136/sssaj2011.0260
|View full text |Cite
|
Sign up to set email alerts
|

A New Method for Developing Equations Applied to the Water Retention Curve

Abstract: The soil water retention curve (WRC) represents the relationship between soil suction and water content. Previous equations for representing the WRC do not include a direct relationship between features of the curve and equation fitting parameters. We present a new method for developing equations for representing empirical data that ensures that features of the curve are directly related to fitting parameters in the equation. The method also ensures that the equation has a simple derivative and is readily inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Of the fitting models, the van Genuchten (1980) and Fredlund and Xing (1994) models appeared to provide SWCCs, which best followed the trends of the measured suction data. The Gould et al (2012) model demonstrated a high value of R 2 for all blends when compared with either the van Genuchten (1980) or the Fredlund and Xing (1994) model. The latter models are simple in their application for prediction of the SWCC, requiring little measured data, when compared with the model of Gould et al, which requires special testing techniques to obtain data for the wet end of the SWCC.…”
Section: Swcc Modelsmentioning
confidence: 85%
See 4 more Smart Citations
“…Of the fitting models, the van Genuchten (1980) and Fredlund and Xing (1994) models appeared to provide SWCCs, which best followed the trends of the measured suction data. The Gould et al (2012) model demonstrated a high value of R 2 for all blends when compared with either the van Genuchten (1980) or the Fredlund and Xing (1994) model. The latter models are simple in their application for prediction of the SWCC, requiring little measured data, when compared with the model of Gould et al, which requires special testing techniques to obtain data for the wet end of the SWCC.…”
Section: Swcc Modelsmentioning
confidence: 85%
“…Gravimetric water content is displayed on the primary vertical axis for the Fredlund and Xing (1994) and Gould et al (2012) models. The degree of saturation is shown on the secondary vertical axis for the van Genuchten (1980) model and the predictive model of Houston et al (2006).…”
Section: Swcc Modelsmentioning
confidence: 99%
See 3 more Smart Citations